Monitoring of Trichloroethene and Tetrachloroethene Content in Soil-Water Environment in Third Phase of Ecological Audit of Land - Pusz Agnieszka; Kulig Andrzej (Archives of Environmental Protection, 2014)
Trichloroethene (TCE) and tetrachloroethene (PCE) are chemical compounds which pose a serious threat for human health. Their specific properties make it possible that these substances may linger in soil and water for many years. These are the reasons why wells with water designed for drinking purposes have been subject of monitoring since 2006. This paper presents the results of monitoring research conducted in the soil-water environment within the framework in third phase of an ecological audit of land. The ecological audit of land made it possible to identify the cause and degree of the degradation, and helped formulate rationale for remedy decisions pertaining to the land (remediation/reclamation). The objective of the paper was to determine the pollution status of the soil-water environment and, subsequently, monitor (in years 2008-2010) the contents of the hazardous substances, namely trichloroethene and tetrachloroethene, within the area of the potential impact of metallurgical plant located in borders of the Main Underground Water Reservoir Wierzbica-Ostrowiec (GZWP 420) in in voivodeship Świętokrzyskie.